As-Sahabah and The Preservation of Hadith - Muhammad Irfan, mirfan (Al Manhal Research Journal, 2021)
One of the issues raised by Some Orientalists scholars against the validity and the authenticity of Ahadith is that they were orally transmitted for over a century before the proper documentation and compilation processes. They argued further that the Traditions were invented trough a chain of narrators down to the Prophet to emphasize either political affiliation or dogmatic doctrine. Put in plain terms, the corpus of the Traditions from the Prophet is alleged to be the product of a large-scale pious forgery that gained momentum in the early second century of Islam. Some Scholars of Hadith have, however, query such postulation. They argued that the Hadith could not have been orally transmitted for over a century without some early written preservation in the first century itself. It can also be added that the availability of literary activities in the Arabian peninsula before the mission of the Prophet Muhammad suggests people’s interest in writing and recording of events. That some curious Sahabah recorded the sayings of the Prophet, therefore, cannot be totally ruled out. This assertion is the main focus of this paper.